Design patterns in PHP and Laravel - Dockins, Kelt (California : Apress, 2017)
This book teaches you design patterns in PHP and Laravel using real-world examples and plenty of humor. Too often design patterns are explained using tricky concepts, when in fact they are easy to use and can enrich your everyday development. Design Patterns in PHP and Laravel aims to break down tricky concepts into humorous and easy-to-recall details, so that you can begin using design patterns easily in your everyday work with PHP and Laravel. You will learn each of the original gang of four design patterns, and how they are relevant to modern PHP and Laravel development. Each pattern is covered with full examples of how it can be used. Written by a working developer who uses these patterns every day, you will easily be able to implement each pattern into your workflow and improve your development.
1. Laravel Basics -- 2. Let's Grow a SOLID Garden -- 3. Abstract Factory -- 4. Builder -- 5. Factory Method -- 6. Prototype -- 7. Singleton -- 8. Simple Factory Method -- 9. Adapter -- 10. Bridge -- 11. Composite -- 12. Decorator -- 13. Façade -- 14. Flyweight -- 15. Proxy -- 16. Chain of Responsibility -- 17. Command -- 18. Interpreter -- 19. Iterator -- 20. Mediator -- 21. Memento -- 22. Observer -- 23. State -- 24. Strategy -- 25. Template Method -- 26. Visitor -- 27. More Resources
Print version record.
Includes bibliographical references and index.
Keywords: Laravel (Software framework); Laravel (Software framework); Software patterns; Software frameworks; Application software -- Development; Web applications -- Development; PHP (Computer program language); Web programming; COMPUTERS -- Programming -- General; COMPUTERS -- Software Development & Engineering; Software patterns; Software frameworks; PHP (Computer program language); Application software -- Development; Electronic books; Electronic books